2023
DOI: 10.1002/eat.23899
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dialysis and renal diseases in patients with anorexia nervosa in Taiwan

Abstract: Objective: To investigate the incidence and risk of renal-related complications in a nationwide cohort of Taiwanese patients with anorexia nervosa (AN).Method: This longitudinal cohort study analyzed the data of 43,951 individualscomprising 2091 patients with AN and their controls matched (1:20) using propensity scores according to sex, age, degree of urbanization of residence, socioeconomic status, and year of diagnosis-from a population-based health insurance database; the study lasted 16 years. We used Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…AN had the most severe outcomes among EDs, including highest relapse and chronicity of weight loss, and highest rates of hospitalization. These outcomes are consistent with the numerous physical health complications that are associated with underweight and malnourishment 72‐77 , and with the importance of early weight gain for a positive disease course 78,79 . BN, instead, had the highest rates of overall improvement and relapse, suggesting a more episodic course compared to other EDs.…”
Section: Discussionsupporting
confidence: 69%
“…AN had the most severe outcomes among EDs, including highest relapse and chronicity of weight loss, and highest rates of hospitalization. These outcomes are consistent with the numerous physical health complications that are associated with underweight and malnourishment 72‐77 , and with the importance of early weight gain for a positive disease course 78,79 . BN, instead, had the highest rates of overall improvement and relapse, suggesting a more episodic course compared to other EDs.…”
Section: Discussionsupporting
confidence: 69%
“…Even though all studies highlight an improvement in renal function with refeeding, some participants still presented varying degrees of impairment, which seemed to worsen with the severity and recurrences of undernutrition, leading to long-term kidney dysfunction with a risk of terminal renal failure in adulthood [ 13 , 16 , 35 – 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over 70% of subjects with AN (independently from the subtypes AN-R or BP) have renal complications at some point in their lives [ 15 ], with a 5.2% prevalence of severe kidney disease, including terminal renal failure after 21 years of AN [ 13 ]. Recently, a cohort study from Taiwan reported that when compared with a control group, 2091 out of over 43,951 individuals had AN and a significantly higher risk of requiring acute dialysis (adjusted hazard ratio 2.10 [95% confidence interval 1.19–3.68]), hypokalaemia, hypovolemia, nephritis, acute renal failure, and chronic renal failure, but no significantly higher risk of end-stage renal disease [ 16 ]. The mortality study by Fichter et al [ 17 ] found that kidney failure was the cause of death for 2 out of 31 AN patients who died from natural causes.…”
Section: Introductionmentioning
confidence: 99%